Clinical and Histological Aspects of Cryptorchidism in Dogs and Cats - Othman J. Ali; Talib G.M. Ali; Goran M. Raouf; O. I. Dana (مجلة الانبار للعلوم البيطرية)
This study was aimed to investigate the incidence of cryptorchidism among dogs and tomcats were undergoing elective neutering. Cryptorchidism is diagnosed through clinical examination, palpation of the scrotum, and the ultrasonic finding of the retained testicles within the inguinal or the abdomen. Eleven cases (11.22%) of cryptorchid were identified from a total of 98 cases (42 dogs and 56 tomcats) that underwent elective castration. It was found that different breeds of dogs and tomcats were affected, including Maltese dog, Anatolian shepherd dog, Terrier dogs, Persian cat, Turkish angora cat, and the Domestic Shorthair cat. The locations of cryptorchid testis were varied from inguinal (3.06%) to intra-abdominal (8.16%) origin with either unilateral (10.2%) or bilateral (1.02%) of retained testis and their ratio was 3:3. The histopathological findings of the cryptorchid testes were showed a decrease and disorganization of the seminiferous tubules with severe hypo-spermatogenesis in both species, dogs, and tomcats. In addition, there was also a typical Sertoli cell-only syndrome (SCOS), which was characterized by larger nuclei and atrophy of many tubules, which were completely replaced by hyaline substances. In conclusion, the occurrence of cryptorchidism in Anatolian Shepherd dogs and the Domestic Shorthair cats were first documented in the literature. Although, no significant differences were found in the incidence of cryptorchidism in both species.